2023
DOI: 10.1002/anie.202218868
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation‐Reduction Molecular Junction Covalent Organic Frameworks for Full Reaction Photosynthesis of H2O2

Abstract: The full reaction photosynthesis of H2O2 that can combine water‐oxidation and oxygen‐reduction without sacrificial agents is highly demanded to maximize the light‐utilization and overcome the complex reaction‐process of anthraquinone‐oxidation. Here, a kind of oxidation‐reduction molecular junction covalent‐organic‐framework (TTF‐BT‐COF) has been synthesized through the covalent‐coupling of tetrathiafulvalene (photo‐oxidation site) and benzothiazole (photo‐reduction site), which presents visible‐light‐adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(75 citation statements)
references
References 67 publications
1
74
0
Order By: Relevance
“…Photoredox catalysis is a green technology with important application prospects in synthetic chemistry, energy, and the environment . Electron or energy transfer occurs for photocatalysis instead of lowering the transition state energy. The process is inseparable from photocatalysts, which ingeniously promotes the generation and assembly of reactive radical/radical ion intermediates under light. For this reason, hydrogen/hydrogen peroxide production from water, carbon dioxide conversion, and degradation of pollutants mediated by photocatalysis have been realized over the past decade. Specially, it is more significant to acquire high value-added fine chemicals via photocatalytic organic transformations. , Photocatalysts represented by organic dyes and transition metal complexes have attracted great attention of synthetic chemists. , However, scientific issues for homogeneous catalytic systems, e.g ., heavy metal residues, toxicity, recyclability, and reusability, remain to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Photoredox catalysis is a green technology with important application prospects in synthetic chemistry, energy, and the environment . Electron or energy transfer occurs for photocatalysis instead of lowering the transition state energy. The process is inseparable from photocatalysts, which ingeniously promotes the generation and assembly of reactive radical/radical ion intermediates under light. For this reason, hydrogen/hydrogen peroxide production from water, carbon dioxide conversion, and degradation of pollutants mediated by photocatalysis have been realized over the past decade. Specially, it is more significant to acquire high value-added fine chemicals via photocatalytic organic transformations. , Photocatalysts represented by organic dyes and transition metal complexes have attracted great attention of synthetic chemists. , However, scientific issues for homogeneous catalytic systems, e.g ., heavy metal residues, toxicity, recyclability, and reusability, remain to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the polymer coating on the carbon electrode greatly improved the long‐term current efficiency through preventing further H 2 O 2 to H 2 O. Covalent organic frameworks (COFs) are a class of crystalline porous polymers connected by covalent bonds with molecular designability, which can be designed for good catalytic activity by introducing catalytic active sites. [ 165 ] An et. al.…”
Section: Photo‐ and Electrocatalysts For H2o2 Productionmentioning
confidence: 99%
“…Photocatalytic production of H 2 O 2 by combination of H 2 O oxidation and O 2 reduction to H 2 O 2 without sacrificial agents is highly required ( vide supra ). 99 A redox molecular-conjugated COF (TTF–BT–COF) was synthesized through the covalent bonding of tetrathiafulvalene (TTF) as a photooxidation site and benzothiazole (BT) as a photoreduction site. 99 This photocatalyst was applied to the generation of H 2 O 2 without sacrificial agents (Scheme 12).…”
Section: Metal–organic Frameworkmentioning
confidence: 99%
“…99 A redox molecular-conjugated COF (TTF–BT–COF) was synthesized through the covalent bonding of tetrathiafulvalene (TTF) as a photooxidation site and benzothiazole (BT) as a photoreduction site. 99 This photocatalyst was applied to the generation of H 2 O 2 without sacrificial agents (Scheme 12). 99 The concentration of H 2 O 2 reached 1.38 mM after 1 h of photoirradiation (entry no.…”
Section: Metal–organic Frameworkmentioning
confidence: 99%
See 1 more Smart Citation